Daqāʾiq al-taʾwīl wa-ḥaqāʾiq al-tanzīl - Ḥasanī, Abu ʼl-Makārim (Miras Maktoob, ISBN: 9789004365452., 2019)
The Qurʾān is a complex text, and it has been regarded as such since the very beginning. Qurʾān interpretation ( tafsīr ) was already practiced by the Prophet's nephew ʿAbdallāh b. al-ʿAbbās, who used folklore and poetry to interpret his uncle's revelations. With the passing of time, Qurʾānic exegesis developed from a mere branch of tradition ( ḥadīth ) into a full-fledged, independent discipline. The earliest Qurʾān commentary in Persian was a translation of Abū Jaʿfar al-Ṭabarī's (d. 311/923) Jāmiʿ al-bayān ʿan taʾwīl āy al-Qurʾān , made in 345/956. The oldest surviving Twelver-Shīʿī commentary to have been composed in Persian is Abu ʼl-Futūḥ al-Rāzī's (d. 552-56/1157-61) Rawḍ al-jinān wa-rūḥ al-janān fī tafsīr al-Qurʾān . Second oldest are two commentaries by Abu ʼl-Makārim Ḥasanī (7th/13th cent.), one of them being his Daqāʾiq al-taʾwīl wa-ḥaqāʾiq al-tanzīl , whose extant part is now published in this volume. A commentary on selected verses only, its unique characteristics and broader context are explained in the editor's introduction.